2010
DOI: 10.1016/j.ijid.2009.11.036
|View full text |Cite
|
Sign up to set email alerts
|

The global war against intestinal parasites—should we use a holistic approach?

Abstract: Intestinal parasite infections have been known to compromise the quality of human life since prehistoric times. Throughout the ages, human civilizations have fought against parasitism, including intestinal parasites. During the second half of the last century, the focus of disease-combating efforts moved to other imminent public health issues, under the notion that the fight against infectious diseases had been won. However, the disease incidence data indicate that these diseases continue to wreak havoc on hum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
165
2
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 166 publications
(178 citation statements)
references
References 61 publications
4
165
2
2
Order By: Relevance
“…Different reports have indicated the presence of strikingly high prevalence rates of the major protozoan and helminth infections in tropical countries, where parasitic diseases remain among the most ubiquitous and serious health problems [2,3]. Lack of clean and safe water, high population density, lack of proper disposal of waste, noncompliance with health standards, lack of adequate washing of vegetables, and consumption of uncooked meat lead to high prevalence of intestinal parasites [4].…”
Section: Introductionmentioning
confidence: 99%
“…Different reports have indicated the presence of strikingly high prevalence rates of the major protozoan and helminth infections in tropical countries, where parasitic diseases remain among the most ubiquitous and serious health problems [2,3]. Lack of clean and safe water, high population density, lack of proper disposal of waste, noncompliance with health standards, lack of adequate washing of vegetables, and consumption of uncooked meat lead to high prevalence of intestinal parasites [4].…”
Section: Introductionmentioning
confidence: 99%
“…Evidences have shown that infections have been closely associated with humans for over 10,000 years [1]. Protozoa and helminthes are the major parasites that infect human.…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of IPIs in each community is indicator of the health status of the area. Some environmental factors such as geographical location, climate, poverty, inadequate health conditions and economic situation, as well as personal factors such as nutrition, safety conditions, health status, cultural habits, literacy, and the high density of population facilitate the prevalence of IPIs [3,17]. Several evaluations were conducted in the different areas of Iran that showed the high prevalence of IPIs [4][5][6][7].…”
Section: Discussionmentioning
confidence: 99%
“…About 450 million people suffer from IPIs that at least 50% of these individuals are children. Lack of health care, the tropical wet climate, lack of access to safe drinking water, poverty, and illiteracy are some factors associated with IPIs [2,3]. In recent years, the prevalence of IPIs has been reported in different areas of Iran [4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%